Evolved Gas Analysis and Kinetics of Catalytic and Non-Catalytic Pyrolysis of Microalgae Chlorella sp. Biomass With Ni/θ-Al2O3 Catalyst via Thermogravimetric Analysis - Farooq, Wasif; Ali, Imtiaz; Raza Naqvi, Salman; Sajid, Mohd; Abbas Khan, Hassnain; Adamu, Sagir (Frontiers in Energy Research, 2021)
This study investigates the efficacy of a prepared Ni/θ-Al2O3 catalyst during the pyrolytic conversion of Parachlorella kessleri HY-6 and compares the results with non-catalytic conversion. The catalyst was characterized by techniques such as Brunauer–Emmett–Teller (BET) for surface area, acidity, and X-ray powder diffraction (XRD). Isocoversional and combined kinetic methods were used to study the pyrolytic kinetics of the process. Ni/θ-Al2O3 was used at 10, 20, and 30% of the algal biomass. The addition of Ni/θ-Al2O3 facilitated the conversion by lowering the mean activation energy during pyrolysis. The catalytic effect was more pronounced at lower and higher conversions. Thermodynamic parameters were also determined. Values of ∆H, and ∆G indicate that the conversion of Parachlorella kessleri HY-6 under pyrolytic conditions with or without a catalyst is endothermic and non-spontaneous. Analysis of evolved gases using Fourier-transform infrared spectroscopy (FTIR) shows the evolved gas behavior during catalytic and non-catalytic pyrolysis of microalgae biomass.